Implementing bandwidth management on computer networks using MIKROTIK router - Kurnia Wira Syahputra; Muhammad Iqbal (Journal of Intelligent Decision Support System (IDSS), 2022)
Today's expansion of information technology is paralleled by the development of computer networks; with tools and software for bandwidth control, the computer network can function properly. Campuses, agencies, and businesses in general require bandwidth management with a Mikrotik router to help overcome the density of traffic that can interfere with computer network connections, where when the network is down or the computer network has problems due to the absence of an even distribution of bandwidth for each user, by Therefore, it is necessary to manage the distribution of the amount of bandwidth, with the goal of achieving the optimal bandwidth capacity for each user. Later, the bandwidth capacity will be allocated to each user according to their internet usage priority in order to optimize the available bandwidth capacity. Bandwidth management, often known as QOS (Quality of Services), is an alternative term for bandwidth management. This application is executed in multiple stages, including network design, implementation, and testing, which is characterized by the availability of a more reliable network.